Malay Arabic Influence in Arabic Writing Skills - Sani, Nurhikmah; Rahmatan, Madah; Putra, Muhammad Hila Azka Harlek; Alfarisi, Diki Ramadhan (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
Learning Malay Arabic writing seems more popular than Arabic writing, therefore it is necessary to know the impact of Malay Arabic writing on Arabic writing and the differences in letters between the two. The purpose of this research is to find out about Malay Arabic and the differences in letters between Malay Arabic and Arabic as well as their impact on learning to write Arabic (insya'). In this research, the method used is library research, data collection is used by looking for sources from books, journals and existing research. The results of this research are 1. Malay Arabic skills have an impact on Arabic writing skills 2. Malay Arabic skills have a negative impact on Arabic writing 3. Malay Arabic writing rules and Arabic writing rules are very different. This research was conducted to find out how Malay Arabic writing and Arabic language writing are and their impact on learning insha'.